The Role of Female Poets in Modern Kurdish Literature - Farhang Muzaffar Muhammad (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper focuses upon some of the female poets in Kurdish literature who have played a major role in establishing Kurdish women`s poetry and their poetic texts, and how their voices become deeper and more feminine. The study will encompass the earliest Kurdish female poet from the classic period - Masture-y Ardalani (1805-1848), one of the most prominent Kurdish poets - and four poets from the modern period, namely Diya Ciwan (b. 1953), Kazhal Ahmed (b. 1967), Nezend Begikhani (b. 1964), and Mahabad Qaradaghi (b. 1966).
Keywords: female poets; Kurdish literature; Ciwan, Diya (1952 -); Ahmed, Kazhal (1967- ); Begikhani , Nezend (1964- ); Qaradaghi, Mahabad (1966- )